An integrated converter and machine control system for MMC-based high power drives - Espinoza, Mauricio; Cardenas, Roberto; Clare, Jon C.; Soto-Sanchez, Diego; Diaz, Matias; Espina, Enrique; Hackl, Christoph (Institute of Electrical and Electronics Engineers, 2018)
The Modular Multilevel Converter (MMC) is a promising topology for high power drive applications. However, large voltage fluctuations are produced in the floating capacitors when the machine is operating with high stator currents at low rotational speed. To compensate these oscillations, relatively large mitigation currents are required to keep the capacitor voltages within an acceptable range. In this paper, a new integrated control scheme is discussed to regulate the voltage fluctuations. The strategy is based on closed-loop vector-control of the voltage fluctuations, maintaining them inside a pre-defined threshold. The proposed control system is also augmented using flux weakening operation of the machine at low rotational speeds. An experimental prototype composed of eighteen power cells, feeding a vector-controlled induction machine in the whole speed range, is used to validate the effectiveness and feasibility of the proposed control strategies.